MODERN CHALLENGES OF DIGITALIZATION OF THE GLOBAL ECONOMIC SPACE: RISKS, BARRIERS AND OPPORTUNITIES (INNOVATIVE ECONOMY, 2025)
Dehtiarov D.S. MODERN CHALLENGES OF DIGITALIZATION OF THE GLOBAL ECONOMIC SPACE: RISKS, BARRIERS AND OPPORTUNITIESPurpose. The aim of the article is to provide a theoretical substantiation and comprehensive analysis of the main challenges of digitalization in the global economic space, and to identify opportunities for overcoming the risks and barriers that arise in the process of digital transformation of the global economy.Methodology of research. The methodological basis of the article is a set of general scientific and special methods of economic analysis that allow for a comprehensive study of the challenges of digitalization in the global economic space. The following methods were used in the research: analysis and synthesis (systematization of scientific approaches to understanding digitalization as a multidimensional global process), inductive and deductive methods (forming the logic of the study: from generalizing the empirical challenges of digital transformation to deriving theoretical propositions), a systematic approach (studying digitalization as a complex social and economic phenomenon encompassing economic, technological, political, and institutional spheres), classification method (typology of digitalization challenges according to substantive criteria (economic, institutional, social, technological, security, etc.), generalization method (forming conclusions and proposals for effective response to digitalization challenges). Findings. The concept of “digitalization challenges” in the context of the global economy has been theoretically substantiated and classified according to economic, social, technological, and institutional characteristics. A comparative analysis of digital policies in countries with different levels of digital maturity was conducted based on DESI index data, which made it possible to identify the key factors for successful digital transformation. The main barriers to overcoming digital challenges were identified, and the potential opportunities of digitalization for sustainable economic development were outlined. Approaches to improving international cooperation in the digital economy, taking into account global imbalances, were proposed.Originality. Further scientific development has been achieved in the study of digitalization, which is a key factor in the transformation of the global economy. However, its dynamic development is accompanied by numerous challenges that require further coordinated global efforts. Practical value. The proposals presented in this paper made it possible to systematize the challenges in four main areas and identify significant differences in the digital policies of countries with different levels of development. In particular, institutional capacity, strategic vision, and investment in innovation are key determinants of the success of digital transformation. Overcoming the identified barriers opens up broad opportunities for improving the efficiency of the global economy, developing digital markets, and ensuring inclusive growth. Further research should focus on developing models of international cooperation in the digital sphere, taking into account the latest challenges.Key words: digitalization, global economy, digital challenges, DESI index, digital transformation, digital policy, digital barriers, sustainable development, international cooperation.
Keywords: digitalization; global economy; digital challenges; DESI index; digital transformation; digital policy; digital barriers; sustainable development; international cooperation